Wheat Production under Long-term Application of Inorganic and Organic Fertilizers in Rice-Wheat System under Rainfed Conditions - Rai, Suresh K.; Khadka, Yajna G. (Nepal Agriculture Research Journal, 2014)
Under rainfed rice-wheat cropping system, experiments were conducted on wheat variety Annapurna-2 from 1998 to 2002 to study the effect of continuous application of inorganic and organic fertilizers in longer run on wheat production and soil properties in alluvial soil of Khumaltar, Lalitpur at 1365 msal. Eleven different fertilizers combinations comprised of inorganic and organic fertilizers were used. The results of the five-year experiment indicate that the applications of optimal level of inorganic fertilizers could supply the plant nutrients to wheat crop to produce sustainable yield. On the other hand, organic fertilizers could help to increase the crop yield and maintain soil fertility at the same time. Residual effect of available phosphorus applied in previous rice crop had significant response on wheat yield. For maintaining soil fertility, application of FYM and incorporation of crop residue into soil are worth practicable. Nepal Agric. Res. J. Vol. 9, 2009, pp. 40-48 DOI: http://dx.doi.org/10.3126/narj.v9i0.11640